GeoGebra as a Learning Mathematical Environment - Dos Santos, José Manuel Dos Santos; Batista Trocado, Alexandre Emanuel (Revista do Instituto GeoGebra Internacional de São Paulo, 2016)
GeoGebra, a software system for dynamic geometry and algebra in the plane, since its inception in 2001, has gone from a dynamic geometry software (DGS), to a powerful computational tool in several areas of mathematics. Powerful algebraic capabilities have joined GeoGebra, an efficient spreadsheet that can deal with many kinds of objects, an algebraic and symbolic calculation system and several graphical views that expand the possibility of multidimensional representations, namely, by using colouring domain techniques, expanded to representations in the Riemann sphere, making this DGS a powerful research tool in mathematics. On the other hand, GeoGebra can create applications easily and export to HTML, and the possibility to quickly integrating these applets in several web platforms provides this DGS with an excellent way to create strong collaborative environments to teach and learn mathematics. Recently was added to GeoGebra powerful capabilities that transform this software a real Learning Mathematical Environment, using the GeoGebraBooks and GeoGebraGroups, plain of collaborative functionality between students and teachers.